Method for preparing hydrogen-type RUT molecular sieve
By replacing tetramethylammonium hydroxide with dimethyldiethylammonium hydroxide and combining stirring, hydrothermal and grinding steps, the toxicity and environmental problems of RUT type molecular sieve synthesis are solved, and an efficient and environmentally friendly hydrogen-type RUT type molecular sieve is achieved. preparation.
Patent Information
- Application Number
- CN202411348600.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The tetramethylammonium hydroxide and fluoride used in the synthesis of existing RUT molecular sieves have a great threat to the environment and human health, and are inexpensive in preparation and have a long crystallization time.
Use low-toxic and environmentally friendly dimethyldiethylammonium hydroxide to replace tetramethylammonium hydroxide, stirring by mixing ethyl orthosilicate, aluminum isopropoxide and water, heating and dealcoholing, hydrothermal treatment, grinding and re- The hydrogen-type RUT molecular sieve is prepared by hydrothermal crystallization, avoiding high-temperature decomposition and the generation of fluorine-containing wastewater.
A safe and environmentally friendly hydrogen-type RUT molecular sieve preparation is achieved, which shortens the synthesis time and improves the preparation efficiency, and does not require the use of highly toxic tetramethylammonium hydroxide and fluoride.
Smart Images

Figure CN119240731A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zeolite molecular sieve synthesis, and more specifically to a method for preparing hydrogen-type RUT molecular sieve. Background Art
[0002] RUT molecular sieve is a microporous molecular sieve with small pores. Its silicon-aluminum ratio is usually between 10 and 75. The hydrogen-type RUT molecular sieve has high activity and selectivity in the isomerization reaction of xylene. RUT molecular sieve usually needs to be hydrothermally synthesized under the condition of tetramethylammonium hydroxide as an organic structure directing agent (Zeolites 1990, 10 (7), 642-649.). Its synthesis conditions are harsh and the crystallization time is long (7-12 days). The tetramethylammonium hydroxide used is very toxic.
[0003] Researchers have also tried to improve the synthesis method under different conditions. The synthesis method in the literature (Zeolites 1994, 14 (8), 675-681.) is to first dissolve tetramethylammonium chloride and ammonium fluoride in water, then add the combined or separate alumina and silica sources in sequence under stirring, stir evenly and transfer to a reactor for crystallization at 170°C for 5 days. However, the product obtained by this method has poor crystallinity and is prone to contain other impurities. The literature (Microporous and mesoporous materials 2001, 43 (3), 329-340.) uses tetramethylammonium hydroxide as a template and FAU zeolite as a crystalline silicon / aluminum source for hydrothermal conversion to obtain RUT zeolite with high crystallinity and purity, and the formation and crystallization rate of RUT zeolite is significantly accelerated. The literature (Microporous and Mesoporous Materials 2008, 113 (1-3), 56-63.) synthesized an all-silicon member of the RUT-type material series, silicon RUB-10, in the SiO2 / H2O / tetrahydropyrrole / NH4F system by using tetrahydropyrrole as a structure-directing agent. RUT-type materials were formed in the presence of tetrahydropyrrole, and the high content of tetrahydropyrrole was considered to be the key factor in the formation of the RUT-type structure.
[0004] The structure-directing agent tetramethylammonium hydroxide used in the synthesis of RUT molecular sieves is highly toxic and corrosive to human skin and eyes, has a high mortality rate, and releases toxic gases when decomposed at high temperatures. Using ammonium fluoride as an auxiliary agent will produce fluorine-containing wastewater, which is harmful to the environment. In addition, the crystallization time required for the preparation of RUT molecular sieves is usually long and the preparation efficiency is low. Summary of the invention
[0005] The present invention provides a method for preparing hydrogen-type RUT molecular sieve, which overcomes the above-mentioned shortcomings of the prior art and uses low-toxic and environmentally friendly dimethyl diethyl ammonium hydroxide to replace the tetramethyl ammonium hydroxide used in the current RUT molecular sieve synthesis process. The method is simple to operate, has fewer synthesis steps and a short synthesis time, does not use highly toxic tetramethyl ammonium hydroxide and fluoride, and has a high application value.
[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a hydrogen-type RUT molecular sieve comprises the following steps: (1) thoroughly mixing and stirring ethyl orthosilicate, aluminum isopropoxide, diethyldimethylammonium hydroxide and water, heating the mixture under stirring conditions to perform a temperature-raising dealcoholization treatment, and obtaining a sol mixture after the dealcoholization is completed; (2) placing the prepared sol mixture into a crystallization kettle and heating it for hydrothermal treatment to obtain a gel; (3) Add water and diethyldimethylammonium hydroxide to the obtained gel and grind it with a grinder. Then, put it into the crystallization kettle again and heat it for hydrothermal crystallization. After the crystallization is completed, the obtained crystallization product is separated into solid and liquid. The obtained solid product is washed with deionized water, and then dried and calcined to obtain the hydrogen-type RUT molecular sieve.
[0007] Furthermore, in the step (1), the molar ratio of tetraethyl orthosilicate, aluminum isopropoxide, diethyldimethylammonium hydroxide and water is tetraethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.02-0.08: 0.20-0.40: 10-30.
[0008] Furthermore, in the step (1), the dealcoholization treatment temperature is 70 to 80° C., and the dealcoholization treatment time is 2 to 5 hours.
[0009] Furthermore, after the dealcoholization treatment in step (1), water needs to be replenished to a water / silicon molar ratio of 10 to 30.
[0010] Furthermore, in the step (2), the hydrothermal treatment temperature is 170-190° C., and the hydrothermal treatment time is 1-2 days.
[0011] Furthermore, in the step (3), the molar ratio of the added water and diethyldimethylammonium hydroxide to the original silicon material in the gel system is water: diethyldimethylammonium hydroxide: silicon = 5-10: 0.10-0.20: 1.0.
[0012] Furthermore, in the grinding process of step (3), 0.6-1.8 mm zirconium oxide ceramic beads are used as grinding media, the grinding speed is 1000-2500 rpm, and the grinding time is 0.5-3 hours.
[0013] Furthermore, in the step (3), the crystallization temperature is 150-170° C., and the crystallization time is 2-3 days.
[0014] Furthermore, after the crystallization is completed in step (3), the drying temperature is 100-200° C., the drying time is 3-12 hours, the calcination temperature is 500-600° C., and the calcination time is 3-6 hours.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. There is no need to use highly toxic tetramethylammonium hydroxide as a structure directing agent, but diethyldimethylammonium hydroxide with low toxicity is used, making the synthesis process safer.
[0016] 2. There is no need to use fluoride as an auxiliary agent, no fluoride-containing wastewater is produced, and the synthesis process is more environmentally friendly.
[0017] 3. The preparation process takes a short time, and the hydrothermal treatment and hydrothermal crystallization time only takes 3 to 5 days, which is conducive to improving the preparation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The XRD spectrum of the hydrogen-type RUT molecular sieve sample synthesized in Example 1 of the present invention; Figure 2 is the XRD spectrum of the hydrogen-type RUT molecular sieve sample synthesized in Example 2 of the present invention; Figure 3 is the XRD spectrum of the hydrogen-type RUT molecular sieve sample synthesized in Example 3 of the present invention; Figure 4 The XRD spectrum of the hydrogen-type RUT molecular sieve sample synthesized in Example 4 of the present invention; Figure 5 The XRD spectrum of the hydrogen-type RUT molecular sieve sample synthesized in Comparative Example 1 of the present invention; Figure 6 The XRD spectrum of the hydrogen-type RUT molecular sieve sample synthesized in Comparative Example 2 of the present invention; DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with the embodiments, which are only used to help understand the present invention. For those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention.
[0020] In the following examples, when analyzing the prepared hydrogen-type RUT molecular sieve, X-ray powder diffraction (XRD) was used for phase analysis, inductively coupled plasma optical emission spectroscopy (ICP-OES) was used to measure the silicon-aluminum content and calculate the silicon-aluminum ratio, and organic base titration was used to measure the B acid concentration (H +ion concentration). Example 1
[0021] A method for preparing hydrogen-type RUT molecular sieve, using tetraethyl orthosilicate as a silicon source, aluminum isopropoxide as an aluminum source, and diethyldimethylammonium hydroxide as a structure directing agent, and the specific synthesis operation is carried out according to the following steps: The first step is to add 12.03 g of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to 17.95 g of water, stir for 5 minutes, add 14.60 g of tetraethyl orthosilicate under stirring, stir for 4-5 hours, and finally add 0.38 g of aluminum isopropoxide (ethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.027: 0.36: 21.38), stir for 12 hours; after being mixed evenly, place in a water bath and heat to 75° C. for dealcoholization for 3 hours, evaporate and remove ethanol produced by hydrolysis of tetraethyl orthosilicate and isopropanol produced by hydrolysis of aluminum isopropoxide, and add water to a water / silicon atom (molar ratio) of 21 to obtain a uniform sol mixture; In the second step, the sol mixture was transferred to a closed stainless steel autoclave lined with polytetrafluoroethylene, heated to 180°C for hydrothermal treatment for 1.5 days, and cooled to room temperature after the hydrothermal treatment to obtain a gel; The third step is to add 5.98 grams of water and 5.15 grams of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to the gel obtained in the second step, the molar ratio of the newly added water: the newly added diethyldimethylammonium hydroxide: the original silicon material in the gel system is 7.80:0.15:1.0, the mixture is loaded into a grinder, 1.0 mm zirconium oxide ceramic beads are used as grinding media, and the mixture is ground at 2000 rpm for 1 hour, the ground mixture is transferred to a closed stainless steel kettle lined with polytetrafluoroethylene, the temperature is raised to 160°C for crystallization for 2 days, and the temperature is lowered to room temperature after the crystallization is completed; the crystallized product is taken out and the solid product is collected by centrifugation, washed with deionized water until neutral, dried at 120°C for 6 hours, and calcined at 550°C for 4 hours to obtain the hydrogen-type RUT molecular sieve.
[0022] The XRD patterns of the obtained samples are shown in the attached Figure 1 As shown. The obtained hydrogen-type RUT molecular sieve sample was sampled and analyzed, and it was found that the silicon-aluminum ratio (Si / Al atomic ratio) of the obtained sample was 35.8, and the B acid concentration (H + ion concentration) is 4.12×10 -4 mol / g. Example 2
[0023] A method for preparing hydrogen-type RUT molecular sieve, using tetraethyl orthosilicate as a silicon source, aluminum isopropoxide as an aluminum source, and diethyldimethylammonium hydroxide as a structure directing agent, and the specific synthesis operation is carried out according to the following steps: The first step is to add 13.37 grams of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to 2.60 grams of water, stir for 5 minutes, add 14.60 grams of tetraethyl orthosilicate under stirring, stir for 4-5 hours, and finally add 0.38 grams of aluminum isopropoxide (ethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.027: 0.40: 10.01), stir for 12 hours; after being mixed evenly, place in a water bath and heat to 70° C. for dealcoholization for 5 hours, evaporate and remove ethanol produced by hydrolysis of tetraethyl orthosilicate and isopropanol produced by hydrolysis of aluminum isopropoxide, and add water to a water / silicon atom (molar ratio) of 10 to obtain a uniform sol mixture; In the second step, the sol mixture was transferred to a closed stainless steel autoclave lined with polytetrafluoroethylene, heated to 170°C for hydrothermal treatment for 2 days, and cooled to room temperature after the hydrothermal treatment to obtain a gel; The third step is to add 10.11 grams of water and 3.35 grams of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to the gel obtained in the second step, the molar ratio of the newly added water: the newly added diethyldimethylammonium hydroxide: the original silicon material in the gel system is 10.00:0.10:1.0, the mixture is loaded into a grinder, 1.8 mm zirconium oxide ceramic beads are used as grinding media, and the mixture is ground at 1000 rpm for 3 hours, the ground mixture is transferred to a closed stainless steel kettle lined with polytetrafluoroethylene, the temperature is raised to 170°C for crystallization for 2 days, and the temperature is lowered to room temperature after the crystallization is completed; the crystallized product is taken out and the solid product is collected by centrifugation, washed with deionized water until neutral, dried at 120°C, and calcined at 550°C to obtain the hydrogen-type RUT molecular sieve.
[0024] The XRD patterns of the obtained samples are shown in the attached Figure 2 As shown. The obtained hydrogen-type RUT molecular sieve sample was sampled and analyzed, and it was found that the silicon-aluminum ratio (Si / Al atomic ratio) of the obtained sample was 35.3, and the B acid concentration (H + ion concentration) is 4.20×10 -4 mol / g. Example 3
[0025] A method for preparing hydrogen-type RUT molecular sieve, using tetraethyl orthosilicate as a silicon source, aluminum isopropoxide as an aluminum source, and diethyldimethylammonium hydroxide as a structure directing agent, and the specific synthesis operation is carried out according to the following steps: The first step is to add 6.70 g of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to 32.83 g of water, stir for 5 minutes, add 14.60 g of tetraethyl orthosilicate under stirring, stir for 4-5 hours, and finally add 0.29 g of aluminum isopropoxide (ethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.02: 0.20: 30.00), stir for 12 hours; after being mixed evenly, place in a water bath and heat to 80° C. for dealcoholization for 2 hours, evaporate and remove ethanol produced by hydrolysis of tetraethyl orthosilicate and isopropanol produced by hydrolysis of aluminum isopropoxide, and add water to a water / silicon atom (molar ratio) of 30 to obtain a uniform sol mixture; In the second step, the sol mixture was transferred to a closed stainless steel autoclave lined with polytetrafluoroethylene, heated to 190°C for hydrothermal treatment for 1 day, and cooled to room temperature after the hydrothermal treatment to obtain a gel; The third step is to add 1.30 grams of water and 6.70 grams of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to the gel obtained in the second step, the molar ratio of the newly added water: the newly added diethyldimethylammonium hydroxide: the original silicon material in the gel system is 5.01:0.20:1.0, the mixture is loaded into a grinder, 0.6 mm zirconium oxide ceramic beads are used as grinding media, and the mixture is ground at 2500 rpm for 0.5 hours, the ground mixture is transferred to a closed stainless steel kettle lined with polytetrafluoroethylene, the temperature is raised to 150°C for crystallization for 3 days, and the temperature is lowered to room temperature after the crystallization is completed; the crystallized product is taken out and the solid product is collected by centrifugation, washed with deionized water until neutral, dried at 100°C for 12 hours, and calcined at 600°C for 3 hours to obtain the hydrogen-type RUT molecular sieve.
[0026] The XRD patterns of the obtained samples are shown in the attached Figure 3 As shown. The obtained hydrogen-type RUT molecular sieve sample was sampled and analyzed, and it was found that the silicon-aluminum ratio (Si / Al atomic ratio) of the obtained sample was 49.0, and the B acid concentration (H + ion concentration) is 3.26×10 -4 mol / g. Example 4
[0027] A method for preparing hydrogen-type RUT molecular sieve, using tetraethyl orthosilicate as a silicon source, aluminum isopropoxide as an aluminum source, and diethyldimethylammonium hydroxide as a structure directing agent, and the specific synthesis operation is carried out according to the following steps: The first step is to add 12.03 grams of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to 17.95 grams of water, stir for 5 minutes, add 14.60 grams of tetraethyl orthosilicate under stirring, stir for 4-5 hours, and finally add 1.14 grams of aluminum isopropoxide (ethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.08: 0.36: 21.38), stir for 12 hours; after being mixed evenly, place in a water bath and heat to 75° C. for dealcoholization for 3 hours, evaporate and remove ethanol produced by hydrolysis of tetraethyl orthosilicate and isopropanol produced by hydrolysis of aluminum isopropoxide, and add water to a water / silicon atom (molar ratio) of 21 to obtain a uniform sol mixture; In the second step, the sol mixture was transferred to a closed stainless steel autoclave lined with polytetrafluoroethylene, heated to 180°C for hydrothermal treatment for 1.5 days, and cooled to room temperature after the hydrothermal treatment to obtain a gel; The third step is to add 5.98 grams of water and 5.15 grams of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to the gel obtained in the second step, the molar ratio of the newly added water: the newly added diethyldimethylammonium hydroxide: the original silicon material in the gel system is 7.80:0.15:1.0, the mixture is loaded into a grinder, 1.0 mm zirconium oxide ceramic beads are used as grinding media, and the mixture is ground at 2000 rpm for 1 hour, the ground mixture is transferred to a closed stainless steel kettle lined with polytetrafluoroethylene, the temperature is raised to 160°C for crystallization for 2 days, and the temperature is lowered to room temperature after the crystallization is completed; the crystallized product is taken out and the solid product is collected by centrifugation, washed with deionized water until neutral, dried at 200°C for 3 hours, and calcined at 500°C for 6 hours to obtain the hydrogen-type RUT molecular sieve.
[0028] The XRD patterns of the obtained samples are shown in the attached Figure 4 As shown. The obtained hydrogen-type RUT molecular sieve sample was sampled and analyzed, and it was found that the silicon-aluminum ratio (Si / Al atomic ratio) of the obtained sample was 15.6, and the B acid concentration (H + Ion concentration) is 9.78×10 -4 mol / g. Comparative Example 1
[0029] Tetraethyl orthosilicate was used as a silicon source, aluminum isopropoxide was used as an aluminum source, and diethyldimethylammonium hydroxide was used as a structure directing agent. The specific synthesis operation was carried out according to the following steps: The first step is to add 17.18 grams of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to 23.93 grams of water, stir for 5 minutes, add 14.60 grams of tetraethyl orthosilicate under stirring, stir for 4 to 5 hours, and finally add 0.38 grams of aluminum isopropoxide (ethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.027: 0.51: 29.18), stir for 12 hours; after being mixed evenly, place in a water bath and heat to 75° C. for dealcoholization for 3 hours, evaporate and remove ethanol produced by hydrolysis of tetraethyl orthosilicate and isopropanol produced by hydrolysis of aluminum isopropoxide, and add water to a water / silicon atom (molar ratio) of 29 to obtain a uniform sol mixture; In the second step, the sol mixture was transferred to a closed stainless steel autoclave lined with polytetrafluoroethylene, heated to 180°C for hydrothermal treatment for 1.5 days, then cooled to 160°C for crystallization for 2 days, and cooled to room temperature after the crystallization was completed; the crystallized product was taken out and centrifuged to collect the solid product, washed with deionized water until neutral, dried at 120°C for 6 hours, and calcined at 550°C for 4 hours to obtain a solid sample. The XRD spectrum of the obtained sample is shown in the attached Figure 5 As shown, it can be seen that the main component is amorphous species. Comparative Example 2
[0030] Tetraethyl orthosilicate was used as a silicon source, aluminum isopropoxide was used as an aluminum source, and diethyldimethylammonium hydroxide was used as a structure directing agent. The specific synthesis operation was carried out according to the following steps: The first step is to add 12.03 g of diethyldimethylammonium hydroxide aqueous solution (mass fraction 25%) to 17.95 g of water, stir for 5 minutes, add 14.60 g of tetraethyl orthosilicate under stirring, stir for 4-5 hours, and finally add 0.38 g of aluminum isopropoxide (ethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.027: 0.36: 21.38), stir for 12 hours; after being mixed evenly, place in a water bath and heat to 75° C. for dealcoholization for 3 hours, evaporate and remove ethanol produced by hydrolysis of tetraethyl orthosilicate and isopropanol produced by hydrolysis of aluminum isopropoxide, and add water to a water / silicon atom (molar ratio) of 21 to obtain a uniform sol mixture; In the second step, the sol mixture was transferred to a closed stainless steel autoclave lined with polytetrafluoroethylene, heated to 180°C for hydrothermal treatment for 1.5 days, then cooled to 160°C for crystallization for 2 days, and cooled to room temperature after the crystallization was completed; the crystallized product was taken out and centrifuged to collect the solid product, washed with deionized water until neutral, dried at 120°C, and calcined at 550°C to obtain a solid sample. The XRD spectrum of the obtained sample is shown in the attached Figure 6 As shown, it can be seen that the main component is amorphous species.
[0031] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing hydrogen-type RUT molecular sieve, characterized in that: The method comprises the following steps: (1) thoroughly mixing and stirring ethyl orthosilicate, aluminum isopropoxide, diethyldimethylammonium hydroxide and water, heating the mixture under stirring conditions to perform a temperature-raising dealcoholization treatment, and obtaining a sol mixture after the dealcoholization is completed; (2) placing the prepared sol mixture into a crystallization kettle and heating it for hydrothermal treatment to obtain a gel; (3) Add water and diethyldimethylammonium hydroxide to the obtained gel and grind it with a grinder. Then, put it into the crystallization kettle again and heat it for hydrothermal crystallization. After the crystallization is completed, the obtained crystallization product is separated into solid and liquid. The obtained solid product is washed with deionized water, and then dried and calcined to obtain the hydrogen-type RUT molecular sieve.
2. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: In the step (1), the molar ratio of tetraethyl orthosilicate, aluminum isopropoxide, diethyldimethylammonium hydroxide and water is tetraethyl orthosilicate: aluminum isopropoxide: diethyldimethylammonium hydroxide: water = 1.0: 0.02-0.08: 0.20-0.40: 10-30.
3. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: The temperature of the dealcoholization treatment in step (1) is 70 to 80° C., and the dealcoholization treatment time is 2 to 5 hours.
4. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: After the dealcoholization treatment in step (1), water needs to be replenished until the molar ratio of water to silicon is 10 to 30.
5. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: In the step (2), the hydrothermal treatment temperature is 170-190° C. and the hydrothermal treatment time is 1-2 days.
6. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: In the step (3), the molar ratio of the added water and diethyldimethylammonium hydroxide to the original silicon material in the gel system is water: diethyldimethylammonium hydroxide: silicon = 5-10: 0.10-0.20: 1.
0.
7. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: In the grinding process of step (3), 0.6-1.8 mm zirconium oxide ceramic beads are used as grinding media, the grinding speed is 1000-2500 rpm, and the grinding time is 0.5-3 hours.
8. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: In the step (3), the crystallization temperature is 150-170° C. and the crystallization time is 2-3 days.
9. The method for preparing hydrogen-type RUT molecular sieve according to claim 1, characterized in that: After the crystallization is completed in the step (3), the drying temperature is 100-200° C., the drying time is 3-12 hours, the calcination temperature is 500-600° C., and the calcination time is 3-6 hours.
Citation Information
Patent Citations
Synthesis method of ITQ-24 zeolite molecular sieve
CN107954440A
Synthesis method of germanium-free IWR zeolite molecular sieve
CN108946755A
DOH zeolite molecular sieve synthesis method
CN109694084A
Method for synthesizing SSZ-13 molecular sieve in sodium-free system at low cost
CN111099630A
Method for synthesizing aluminum-rich * MRE zeolite molecular sieve in one step by using organic template agent
CN111573694A